Multi-institutional Analysis of Prognostic Factors and Outcomes after Hypofractionated Stereotactic Radiotherapy to the Resection Cavity in Patients with Brain Metastases - Eitz, Kerstin A.; Lo, Simon S.; Soliman, Hany; Sahgal, Arjun; Theriault, Aimee; Pinkham, Mark. B.; Foote, Matthew C.; Song, Andrew J.; Shi, Wenyin; Redmond, Kristin J.; Gui, Chenchen; Kumar, Aryavarta M. S.; et al. (JAMA Oncology, 2020)
Importance: For brain metastases, the combination of neurosurgical resection and postoperative hypofractionated stereotactic radiotherapy (HSRT) is an emerging therapeutic approach preferred to the prior practice of postoperative whole-brain radiotherapy. However, mature large-scale outcome data are lacking. Objective: To evaluate outcomes and prognostic factors after HSRT to the resection cavity in patients with brain metastases. Design, Setting, and Participants: An international, multi-institutional cohort study was performed in 558 patients with resected brain metastases and postoperative HSRT treated between December 1, 2003, and October 31, 2019, in 1 of 6 participating centers. Exclusion criteria were prior cranial radiotherapy (including whole-brain radiotherapy) and early termination of treatment. Exposures: A median total dose of 30 Gy (range, 18-35 Gy) and a dose per fraction of 6 Gy (range, 5-10.7 Gy) were applied. Main Outcomes and Measures: The primary end points were overall survival, local control (LC), and the analysis of prognostic factors associated with overall survival and LC. Secondary end points included distant intracranial failure, distant progression, and the incidence of neurologic toxicity. Results: A total of 558 patients (mean [SD] age, 61 [0.50] years; 301 [53.9%] female) with 581 resected cavities were analyzed. The median follow-up was 12.3 months (interquartile range, 5.0-25.3 months). Overall survival was 65% at 1 year, 46% at 2 years, and 33% at 3 years, whereas LC was 84% at 1 year, 75% at 2 years, and 71% at 3 years. Radiation necrosis was present in 48 patients (8.6%) and leptomeningeal disease in 73 patients (13.1%). Neurologic toxic events according to the Common Terminology Criteria for Adverse Events grade 3 or higher occurred in 16 patients (2.8%) less than 6 months and 24 patients (4.1%) greater than 6 months after treatment. Multivariate analysis identified a Karnofsky Performance Status score of 80% or greater (hazard ratio [HR], 0.61; 95% CI, 0.46-0.82; P <.001), 22 to 33 days between resection and radiotherapy (HR, 1.50; 95% CI, 1.07-2.10; P =.02), and a controlled primary tumor (HR, 0.69; 95% CI, 0.52-0.90; P =.007) as prognostic factors associated with overall survival. For LC, a single brain metastasis (HR, 0.57; 95% CI, 0.35-0.93; P =.03) and a controlled primary tumor (HR, 0.59; 95% CI, 0.39-0.92; P =.02) were significant in the multivariate analysis. Conclusions and Relevance: To date, this cohort study includes one of the largest series of patients with brain metastases and postoperative HSRT and appears to confirm an excellent risk-benefit profile of local HSRT to the resection cavity. Additional studies will help determine radiation dose-volume parameters and provide a better understanding of synergistic effects with systemic and immunotherapies.
CRIS-Team Scopus Importer:2023-03-08